An Automated Refusal Conversion Strategy for Web Surveys. Issue 4 (November 2019) - Lewis, Taylor; Gorsak, Mark; Yount, Naomi
This article presents results from an experiment conducted during the web-based 2017 Federal Employee Viewpoint Survey (FEVS) to evaluate an automated refusal conversion strategy whereby a sample of individuals was given the opportunity to opt out from the survey and stop receiving additional e-mail reminders. Before being added to the unsubscribe list, however, the individual was asked to cite the primary reason for choosing not to take the FEVS. A randomly assigned subset was given a last-moment appeal, tailored to the reason provided, at which point the individual could either confirm desiring to opt out or navigate to the start of the survey. Because the complementary subset did not receive the appeal, we are able to report on the efficacy of the strategy in convincing individuals who may not have been initially inclined to participate to do so.